THE SPIN COATING METHOD, FOR THE DEPOSITION OF THIN LAYERS, USED IN IMPLANTOLOGY - Nicoleta-Maria MIHUT (Fiabilitate şi Durabilitate)
The paper presents the Spin Coating Method of depositing thin layers as a good alternative to increase the antimicrobial activity of the metallic materials used in impantology.